Analisis Kesulitan Menyelesaikan Soal Geometri Ditinjau Dari Level Berpikir Pada Siswa Kelas VIII MTs. Muhammadiyah Waru Baki SukoharjoTahun Ajaran 2015/2016 - Cahyaningrum, Ana Octavia, Dra. Nining Setyaningsih, M.Si (2016)
ABSTRACT Ana Octavia Cahyaningrum/A410120181. ANALYSIS OF DIFFICULTIES RESOLVING PROBLEMS GEOMETRY VIEWED FROM THE LEVEL OF THOUGHT AN GRADE VIII STUDENTS MTs. MUHAMMADIYAH OF WARU BAKI SUKOHARJO 2015/2016 ACADEMIC YEAR. Essay. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. June 2016. The research aimed to describe the location of the difficulties experienced by students and determine to the find out the factor causing of the difficulties in completing the eighth grade students on the subject matter of geometry tangent to the circle which is seen from Van Hiele levels of thinking. This research is a qualitative research. The subjects of this research are 6 students of class VIII MTs. Muhammadiyah Waru Baki, Sukoharjo. Data collection techniques using written tests, interviews, documentation and observation. Data analysis techniques used in this research is to reduce the data, presenting data and draw conclusions. Van Hiele levels of thingking consists of five levels but researchers only use three levels, namely visualization, analysis and informal deduction. The results of this research stated that the location of the student's difficulties occur at the level of visualization and informal deduction. Factors causing difficulties students in general is the tendency of students to memorize without understanding the concept, the lack of students' understanding of the meaning of the problems and the lack of practicing solving math problems. Keyword : geometry, difficulties, geometry level of thought